(untitled) - Felder, Richard M. (Hoboken, N.J., 2017)
Felder's Elementary Principles of Chemical Processes prepares students to formulate and solve material and energy balances in chemical process systems and lays the foundation for subsequent courses in chemical engineering. The text provides a realistic, informative, and positive introduction to the practice of chemical engineering.
Keywords: Quá trình hóa học,Chemical processes